Technical and Financial Feasibility Analysis of Pumpkin’s Crackers Business Development with Chopper Machines in Small Enterprise - Mustaniroh, Siti Asmaul; Mahdami, Safira Aziz; Effendi, Mas'ud (Jurnal Teknologi Pertanian, 2011)
This study aims to determine the technical feasibility and financial business development of pumpkin’s crackers with chopper machines to fulfill the shortage of pumpkin’s chips production. The importance of doing the technical and financial feasibility analysis is to analyze whether the planned business technicaly profitable enough to be carried out or not. Research methods in this research are organopleptic test, and technical and financial feasibility analysis. The results of organoleptic tests of taste, aroma, color and texture that consumers prefer are waluh crackers that produced using a chopper machine. The results of the technical and financial feasibility analysis demonstrate that business development is feasible to conduct.   Keywords: pumpkin’s crackers, technical and financial feasibility analysis, chopper machines